(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2019)
Franchising in the Balkan area has been present since the late 1980s and early 1990s when the countries of the so-called communist block started a transition to a market economy and opened their borders to new companies, “new” ideas, foreign companies, and foreign capital. Franchising was introduced mainly by foreign companies, which triggered activities of local entrepreneurs who started to use franchising as their growth strategy. Although almost 30 years have passed since then, franchising in those countries is in different phases of development, ranging from very early to very developed phases of development. The paper will examine the current status of franchising in several countries in the Balkan area (i.e., Slovenia, Croatia, Serbia, and Macedonia) and present current opportunities for and barriers to further development. In the first part of the paper, we will give a brief introduction to franchising and several theories used for explaining franchising. In the second part, the current situation in relation to franchising in several countries in the Balkan area will be presented based on the current number of franchising systems and the existing legal framework. In the last part, similarities between the countries under study will be examined, and based on the findings, a conclusion will be made together with proposals for further research.